THE PROCESS OF COMMUNICATION PROVIDES OPPORTUNITIES FOR THE PERSONAL DEVELOPMENT OF SCHOOLCHILDREN - Sultanova V. K.; Khabipov M. A. (Web of Journals Publishing, 2025)
This article examines the opportunities for personal growth of secondary school students in the process of communication.
Keywords: Personality of students, communication process, friendly relations, joint activity, communication skills.